Effects of diesel exhaust inhalation on cognitive performance in human volunteers: A randomized controlled crossover study - Jason Curran; A.J. Hirsch Allen; Christopher F. Rider; Robin Shutt; Chris Carlsten (Environment International)
Background: Mounting evidence links exposure to traffic-related air pollution (TRAP) to impairment in cognitive functioning. Objectives: To determine if short-term, controlled exposure to diesel exhaust (DE) adversely affects one or more cognitive function domains. Methods: We carried out a double-blinded crossover design with 28 healthy, adult volunteers. Volunteers were exposed to two conditions for 120 min each, on separate order-randomized occasions: filtered air (FA) and DE (300 µg/m3 PM2.5) at the Air Pollution Exposure Laboratory (APEL) at Vancouver General Hospital (VGH). Volunteers were blinded to the two exposure conditions. Volunteers completed five computerised neuropsychological tests of the Cambridge Neuropsychological Test Automated Battery (CANTAB) prior to (2-hr before) and at three timepoints following each exposure condition (0-hr, 3-h post-, and 24-h post-exposure). The selected CANTAB tests were related to five cognitive domains – attention, spatial working memory, strategy use, executive function, and processing speed. We hypothesized that short-term diesel exposure would adversely affect one or more cognitive function domains. Results: Following screening, 15 volunteers were randomized to receive FA followed by DE and 14 volunteers were randomized to receive the exposures in the reverse sequence. A total of 28 volunteers contributed to the final analysis. Short-term exposure to DE was associated with slower reaction times in the Reaction Time Index task. DE was associated with a decrease of 18.2 ms (p = 0.05) in simple reaction time and 23.5 ms (p = 0.04) in five-choice reaction time. Conclusions: This first study to investigate the effects of TRAP on the cognitive performance of humans in a controlled environment shows slowed reaction times similar to those previously demonstrated with blood alcohol levels of 0.05%. Important implications exist for workers in occupations where attention and reaction time are connected to safety and performance.